Nanoparticles Targeting Receptors on Breast Cancer for Efficient Delivery of Chemotherapeutics - Jahan, Sulltana (Biomedicines, 2021)
The journey of chemotherapeutic drugs from the site of administration to the site of action is confronted by several factors including low bioavailability, uneven distribution in major organs, limited accessibility of drug molecules to the distant tumor tissues, and lower therapeutic indexes. These unavoidable features of classical chemotherapeutics necessitate an additional high, repetitive dose of drugs to obtain maximum therapeutic responses with the result of unintended adverse side effects. An erratic tumor microenvironment, notable drawbacks of conventional chemotherapy, and multidrug-resistant mechanisms of breast cancer cells warrant precisely designed therapeutics for the treatment of cancers. In recent decades, nanoparticles have been deployed for the delivery of standard anticancer drugs to maximize the therapeutic potency while minimizing the adverse effects to increase the quality and span of life. Several organic and inorganic nanoplatforms that have been designed exploiting the distinctive features of the tumor microenvironment and tumor cells offer favorable physicochemical properties and pharmacokinetic profiles of a parent drug, with delivery of higher amounts of the drug to the pathological site and its controlled release, thereby improving the balance between its efficacy and toxicity. Advances to this front have included design and construction of targeted nanoparticles by conjugating homing devices like peptide, ligand, and Fab on the surface of nanomaterials to navigate nanoparticledrug complexes towards the target tumor cell with minimal destruction of healthy cells. Furthermore, actively targeting nanoparticles can facilitate the delivery and cellular uptake of nanoparticle-loaded drug constructs via binding with specific receptors expressed aberrantly on the surface of a tumor cell. Herein, we present an overview of the principle of targeted delivery approaches, exploiting drug-nanoparticle conjugates with multiple targeting moieties to target specific receptors of breast cancer cells and highlighting therapeutic evaluation in preclinical studies. We conclude that an understanding of the translational gap and challenges would show the possible future directions to foster the development of novel targeted nanotherapeutics.